Strategies for hepatitis B booster vaccination among children: an 8-year prospective cohort study - Yan Qiu; Jing-Jing Ren; Zi-Kang Wu; Ling-Zhi Shen; Huan Shan; Xue-Wei Dai; Jing Li; Ying Liu; Wen Ren; Jun Yao; Lan-Juan Li (Taylor & Francis Group, 2020)
Debate continues regarding the need for a booster vaccination in children who received a universal infant hepatitis B virus (HBV) vaccination. The aim was to explore the need and the strategies for the booster HBV vaccination. 8-year prospective cohort study was conducted among children aged 5-15 years in 2009-2010 in Zhejiang Province. The participants were divided into groups A (<0.1 mIU/mL), B (0.1 to < 1 mIU/mL) and C (1 to <10 mIU/mL) according to the pre-booster anti-HBs antibody levels. 5 μg (group I), 10 μg (group II), 20 μg hepatitis B vaccines (group III) or 5 μg hepatitis A and B (HAB) vaccines (group IV) with 0-1-6-month schedule were randomly administered to children negative for all markers. Blood samples were collected at baseline HBV marker testing, 1 month after the first dose, 1 month, 1 year, 5 years and 8 years after the third dose. Among 4170 children, 2326 (55.8%) were negative for all HBV markers. Group II showed the highest seropositive rates of 92.8%, 99.7%, 97.6%, 90.3% and 83.4% with GMTs of 4194.5 mIU/ml, 4163.9 mIU/ml, 466.9 mIU/ml, 190.6 mIU/ml, 122.6 mIU/ml from 1 month after dose 1 to 8 years after dose 3, respectively (P < .01). Participants in group C showed seropositive rates of 98.9%, 99.9%, 99.5%, 95.5%, 92.8% after the revaccination with GMTs of 6519.6 mIU/ml, 5267.4 mIU/ml, 547.1 mIU/ml, 249.5 mIU/ml, 155.3 mIU/ml, respectively, higher than group A and B (P < .001), except 1 month after the third dose. The 10 μg of HBV vaccine with a 0-1-6-month booster regimen may elicit robust responses and persist for 8 years or longer. Additionally, 1-dose revaccination maybe suitable for children with 1 to < 10 mIU/ml anti-HBs titers.